Design and construction of an omnidirectional sound source with inverse filtering approach for optimization. (October 2018) - Ibarra, David; Ledesma, Rodrigo; Lopez, Edgar
Graphical abstract: Abstract: The aim of this study is to design an efficient omnidirectional point source whose analysis and design is also described here. The point source was designed with the help of MATLAB and SolidWorks software respectively for calculating the optimal dimensions. This point source is composed of a base in which the speaker is settle, and a cone that provides the omnidirectionality. Three different bases with three different cones were implemented and tested to determine which combination gives less reflection on rear part of cabinet. To enhance a flat response and true omnidirectionality, an Inverse Filtering Method will be introduced to the study. As a result, we observe that the point source is best suited with a cylindrical base and a 20 cm long cone. The radiation patterns showed omnidirectional results for frequencies lower than 15 kHz, and maximum deviation of 4 dB for 30 degrees.